2006
DOI: 10.1007/s10484-006-9024-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Respiratory Muscle Biofeedback Procedure–Effects on Heart Rate and Dyspnea

Abstract: Patients with respiratory diseases or anxiety frequently complain about dyspnea, which may be partly related to chronic tension of respiratory muscles and/or dynamic hyperinflation. In two experiments we tested a biofeedback technique that recorded electromyographic (EMG) activity from a bipolar surface electrode placement over the right external intercostal muscles with visual signal feedback. Healthy participants were tested in their ability to alter the signal. Heart rate was measured continuously throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In a pilot study with healthy individuals, we used electromyogram (EMG) biofeedback targeting the tension levels of intercostal muscles (12). Our findings showed substantial increases in dyspnea during periods of tension.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In a pilot study with healthy individuals, we used electromyogram (EMG) biofeedback targeting the tension levels of intercostal muscles (12). Our findings showed substantial increases in dyspnea during periods of tension.…”
Section: Introductionmentioning
confidence: 90%
“…Our sample was also limited in that we only recruited from an undergraduate student population. Participants' qualitative reports of our pilot study also suggested that more than one respiratory muscle site was activated by the biofeedback task, with some participants describing in the debriefing session maneuvers such as tension of chest muscles and/or the shoulders or abdomen to manipulate the biofeedback signal (12). With regard to our measures of respiratory muscle tension, as with any surface electrode placement, we did not measure the activity of individual muscles but more nonspecific activity at a particular muscle site (51).…”
Section: Respiratory Muscle Tension and Anxietymentioning
confidence: 98%
See 1 more Smart Citation